LEVELS OF BODY COMPOSITION OF PRESCHOOL CHILDREN FROM THE PRIVATE SYSTEM OF EDUCATION IN THE CITY OF BARBALHA-CE, BRAZIL (Fiep Bulletin - online, 2014)
The body composition (BC) is a parameter that subsidizes the attendance in stage of development and growth of an individual a long one's life. The objective of this study is to analyze the levels of body composition in preschool children. The sample was composed by 51 children, at the age from 2 to 7 years old in the city of Barbalha - CE, submitted to body mass (kg), stature (cm) and skin folds (mm) measures at the biceps, triceps, to sub scapular and supra-iliac areas and perimetria (cm) of the arm, fist, abdomen, hip, thigh and calf from both sides, right and left. For the analysis of the data was used statistical program SPSS version 13.0 for descriptive and inferencial statistics, with level of 5% of significance. The results had demonstrated that 58.8% of the evaluated children are normal weight, 23.5% are overweight, 15.7% obese and 2% are below the normal weight. Among male children, 53.6% are normal weight, 21.4% obese and overweight, and 3.6% are below the normal weight. Among female ones, 65.22% are with the normal weight, 26.09% are overweight and 8.7% are obese. In relation to the distribution of regional fat, one evidenced that the triceps folds and supra-iliac are the areas of higher predominance of body fat among the surveyed ones, as much for the complete group as to the analysis of genders, being the highest average values found at the female group. Conclusion: The degree of obesity and overweight are high in the sample, in special in the male group; the predominance of deposit of body fat at the triceps and supra- iliac areas in both the gender, presents  higher values in the female group, what one can suggest an initial trend for a higher accumulation of fat in the areas of the trunk, being it future indicator of cardiac risk.
Keywords: assessment; body composition; preschool